Meningkatkan kemampuan mengenal bilangan melalui permainan dadu di kelompok bermain Paud terpadu Qathrun Nada Banjarmasin - Sakerani Sakerani; Hayatun Nufus (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
Children's cognitive ability in counting is still very low because other efforts need to be made to improve the child's ability, in this case the researcher tries to play dice for children playing group (KB) in stating the sequence of numbers 1-10, with the hope that the child's ability will increase. Cognitive research that becomes the focus of research is a process of thinking, namely the ability of individuals to connect, assess and consider an event or event. Cognitive processes related to the level of intelligence that characterizes a person with various interests, especially aimed at ideas and learning. Classroom action research is a research that is carried out systematically, reflective of